The proselyte and the prophet: character development in Targum Ruth - Brady, Christian M. M. (Supplement to Aramaic studies, 2016)
‎Contents -- ‎Editor's Note -- ‎Acknowledgements -- ‎Abbreviations -- ‎General Abbreviations -- ‎Rabbinic Texts -- ‎Reference Works -- ‎Sigla -- ‎Chapter 1. Introduction -- ‎The Book of Ruth -- ‎Chapter 1 -- ‎Chapter 2 -- ‎Chapter 3 -- ‎Chapter 4 -- ‎The Targum of Ruth -- ‎Manuscript Tradition -- ‎Translation -- ‎Origins -- ‎An Exegetical Commentary -- ‎Chapter 2. Transcription and Translation -- ‎Targum Ruth-Valmadonna No. 1 -- ‎Chapter 3. Exegetical Commentary -- ‎Tg. Ruth Chapter 1 -- ‎Tg. Ruth 1:1-5-Prologue -- ‎Translation